Identifying the influence of project delivery system (PDS) characteristics on green construction project performance - Mas Pertiwi, I G A Istri; Zaika, Yulvi; Puspa Negara, Kartika; Solimun, Solimun; Agung Wibowo, Mochamad (Eastern-European Journal of Enterprise Technologies, 2024)
This study examines the influence of Project Delivery System (PDS) features on green construction project performance by comparing Design-Bid-Build (DBB), Design-Build (DB), and Construction Management (CM) methods. The research problem is to analyze the influence of key characteristics (leadership, communication, mindset, teamwork, team chemistry, experience, competence) of the three PDS methods on achieving green construction project performance. The research objects were 109 respondents (team leader, vice president manager, project manager, site manager, site engineer, general superintendent, and supervisor) in five major cities in Indonesia. The results of the MANOVA analysis showed that leadership was the most influential factor in the three methods. CM excels in time, quality, and green building performance, DB excels in Occupational Health and Safety (OHS), and DBB excels in cost. Experience and competence are less influential factors, thus concluding that soft skills play a significant role in the successful implementation of green construction projects, providing valuable insights for industry practitioners and emphasizing the need to prioritize the development of leadership and interpersonal skills alongside technical expertise when implementing green construction projects through various PDS methods in Indonesia, which ultimately contributes to the advancement of sustainable construction practices in the rapidly growing building sector in the region. These findings provide insights for selecting optimal PDS methods in green construction projects